Fe / Mn-SNC double-monatomic nanometer material with multi-enzyme activity and preparation method and application of Fe / Mn-SNC double-monatomic nanometer material

By designing Fe/Mn-SNC double single atom nanomaterials, the problems of natural enzymes in the field of biomedical science have been solved, efficient killing of bacteria such as MRSA and broad-spectrum antibacterials are achieved, and drug resistance problems are avoided. It is of great importance scientific and commercial value.

CN119140839AActive Publication Date: 2024-12-17CHINA REHABILITATION SCIENCE INSTITUTE (DISABILITY PREVENTION AND CONTROL RESEARCH CENTER OF CHINA DISABLED PERSONS FEDERATION)

Patent Information

Application Number
CN202411284873.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-17
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

The application of natural enzymes in the biomedical field is limited by problems such as difficult preparation, volatility, high cost and difficulty in recycling and preservation. The existing artificial nanoenzyme catalysts have problems with insufficient drug resistance and universality in antibacterial effects.

Method used

Design and develop Fe/Mn-SNC double single atom nanomaterials with multi-enzyme activity, prepare double single atom nanoenzymes with Yolk-Shell structure through one-step pyrolysis method, and synthesize morphology using local fine regulation strategies to realize oxidase-like enzymes , the activities of glutathione-like oxidase, superoxide dismutase and peroxidase can generate ROS without adding ROS, quickly killing bacteria.

Benefits of technology

It has achieved efficient killing of bacteria such as methicillin-resistant Staphylococcus aureus (MRSA), and is not prone to drug resistance. It has broad-spectrum antibacterial effects and important scientific significance and commercial value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140839A_ABST
    Figure CN119140839A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of medical nano-materials, and particularly relates to a Fe / Mn-SNC double-monatomic nano-material with multienzyme activity and a preparation method and application of the Fe / Mn-SNC double-monatomic nano-material. The designed and developed Fe / Mn-SNC double monatomic adopts a local fine regulation strategy, the surface and space structure of a host are finely regulated to bear the relationship between metal double active sites, the double monatomic nano-enzyme with the Yolk-Shell structure morphology is synthesized through a one-step pyrolysis method and a ligand etching pyrolysis strategy, the structural property is stable, the rich active sites are achieved, and the nano-enzyme can be used for preparing the metal double monatomic nano-enzyme with the Yolk-Shell structure. The enzyme-like activity can be achieved to the maximum extent. The nano material has multi-enzyme activity, can initiate cascade reaction of the nano material, so that rich ROS (reactive oxygen species) is generated, an antibacterial effect is achieved, and the nano material does not have drug resistance and is high in universality, so that the nano material has important scientific significance and huge commercial value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of medical nanomaterials, and specifically relates to a Fe / Mn-SNC double single-atom nanomaterial with multi-enzyme activity, a preparation method and application thereof. Background Art

[0002] After billions of years of evolution, natural enzymes have demonstrated versatile catalytic capabilities, enabling efficient cascade reactions in different biological systems while maintaining excellent product selectivity. However, some inherent fragility of natural enzymes, such as difficulty in preparation, variability, high cost, and difficulty in recycling and preservation, have hindered their practical application in the biomedical field.

[0003] To address these issues, attempts have been made to artificially mimic enzymes since the 1970s by integrating metal cofactors and catalytic active sites into scaffolds (mainly proteins), which are called artificial nanozymes. In this context, many nanocatalysts called single-atom catalysts (SACs) with uniformly coordinated catalytic sites have been widely synthesized, characterized, and realized. This evolving toolbox provides biological scientists with new avenues to revisit complex enzyme catalysis and design advanced artificial enzymes.

[0004] Based on this, the inventors designed and developed a new type of Fe / Mn-SNC double single-atom nanomaterial with multi-enzyme activity. The study found that the Fe / Mn-SNC can undergo a cascade reaction and self-generate ROS without the addition of ROS. It can quickly kill bacteria, has no drug resistance, and has strong universality. Summary of the invention

[0005] In order to overcome the defects and shortcomings of the prior art, the present invention provides a novel Fe / Mn-SNC double single-atom nanomaterial with multi-enzyme activity and its preparation method and use. The material can quickly kill bacteria (especially methicillin-resistant Staphylococcus aureus, MRSA) and has no drug resistance, so it has important scientific significance and huge commercial value.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0007] In a first aspect, the present invention provides a method for preparing a Fe / Mn-SNC double single-atom nanomaterial having multi-enzyme activity, the preparation method comprising the following steps:

[0008] Step 1: Preparation of powdered FeMn-MOF: 1-5 g Zn(NO3)2·6H2O, 20-80 mg Mn(OAc)2 and 20-80 mg Fe(NO3)2·9H2O are added to 50-100 mL organic solvent at the same time, stirred to prepare a metal precursor solution; 1-5 g 2-methylimidazole is dissolved in 50-100 mL organic solvent to prepare a ligand solution; then, the metal precursor solution is immediately added to the ligand solution, stirred continuously, washed several times with an organic solvent, and dried in a vacuum oven overnight to obtain powdered FeMn-MOF;

[0009] Step 2: Preparation of FeMn-SNC DASC using a one-step pyrolysis strategy: 10-50 mg sulfur powder was uniformly mixed with 0.5-5 g dicyandiamide and loaded into a porcelain boat and placed in the upstream of the tube furnace. 50-150 mg FeMn MOF powder was placed in the porcelain boat and placed in the downstream of the tube furnace. The mixture was then heated at 800-1200 °C for 5 °C min -1 The FeMn-SNCDASC was obtained by pyrolysis in Ar atmosphere at a rate of 1.5 %.

[0010] As an optional manner, in the above preparation method, the preparation method comprises the following steps:

[0011] Step 1: Preparation of powdered FeMn-MOF: Add 2-4 g Zn(NO3)2·6H2O, 50-70 mg Mn(OAc)2 and 50-70 mg Fe(NO3)2·9H2O to 70-90 mL organic solvent at the same time, stir for 20-40 min to prepare a metal precursor solution; dissolve 2-4 g 2-methylimidazole in 70-90 mL organic solvent to prepare a ligand solution; then, immediately add the above metal precursor solution to the above ligand solution, continue stirring for 4-6 h, wash with organic solvent several times, and dry in a vacuum oven overnight to obtain powdered FeMn-MOF;

[0012] Step 2: Preparation of FeMn-SNC DASC using a one-step pyrolysis strategy: 20-40 mg sulfur powder was uniformly mixed with 0.5-2 g dicyandiamide and loaded into a porcelain boat and placed in the upstream of the tube furnace. 80-120 mg FeMn MOF powder was placed in the porcelain boat and placed in the downstream of the tube furnace. The mixture was then heated at 900-1100 °C for 5 °C min -1 The FeMn-SNC DASC was obtained by pyrolysis in Ar atmosphere at a rate of 1 to 5 h.

[0013] As an optional manner, in the above preparation method, the preparation method comprises the following steps:

[0014] Step 1: Preparation of powdered FeMn-MOF: Add 2.94g Zn(NO3)2·6H2O and 60mg Mn(OAc)2+60mg Fe(NO3)2·9H2O to 80mL anhydrous methanol at the same time and stir for 30min to prepare a metal precursor solution. Dissolve 3.24g 2-methylimidazole in 80mL methanol solution to prepare a ligand solution. Then, immediately add the above metal precursor solution to the above ligand solution and continue stirring for 5h. Wash three times with methanol and dry in a vacuum oven at 60°C overnight to obtain powdered FeMn-MOF.

[0015] Step 2: FeMn-SNC DASC was prepared by one-step pyrolysis strategy: 30 mg sulfur powder was uniformly mixed with 1 g dicyandiamide and loaded into a porcelain boat and placed in the upstream of the tube furnace. 100 mg FeMn MOF powder was placed in the porcelain boat and placed in the downstream of the tube furnace. Then, the mixture was heated at 1000 °C for 5 °C min. -1 The FeMn-SNC DASC was obtained by pyrolysis under Ar atmosphere at a rate of 2 h.

[0016] As an optional mode, in the above preparation method, the organic solvent is methanol.

[0017] In a second aspect, the present invention provides a Fe / Mn-SNC double single-atom nanomaterial prepared by the preparation method described in the first aspect.

[0018] As an optional manner, in the above nanomaterial, the nanomaterial has a Yolk-Shell structure.

[0019] As an optional manner, in the above-mentioned nanomaterial, the multi-enzyme activity includes oxidase (OXD)-like, glutathione oxidase (GPx)-like, superoxide dismutase (SOD)-like and peroxidase (POD)-like activities.

[0020] As an optional manner, in the above-mentioned nanomaterial, the multi-enzyme activity is oxidase (OXD)-like, glutathione oxidase (GPx)-like, superoxide dismutase (SOD)-like and peroxidase (POD)-like activities.

[0021] In a third aspect, the present invention provides use of the nanomaterial described in the second aspect in preparing an antibacterial agent for removing bacteria.

[0022] As an optional mode, in the above use, the antibacterial agent has a broad-spectrum antibacterial effect.

[0023] As an alternative, in the above use, the bacteria include Escherichia coli and methicillin-resistant Staphylococcus aureus (MRSA).

[0024] Compared with the prior art, the present invention has the following advantages and positive effects:

[0025] (1) The Fe / Mn-SNC double single atom designed and developed by the present invention adopts a local fine-tuning strategy to finely adjust the relationship between the host surface and the spatial structure to carry the metal double active sites. Through a one-step pyrolysis method and a ligand-etching pyrolysis strategy, a Yolk-Shell structured double single-atom nanozyme is synthesized. The structure is stable, has abundant active sites, and can maximize enzyme-like activity.

[0026] (2) The nanomaterial designed and developed by the present invention has multi-enzyme activity and can trigger its own cascade reaction, thereby generating abundant ROS, playing an antibacterial role (especially methicillin-resistant Staphylococcus aureus, MRSA), and has no drug resistance and strong universality. Therefore, it has important scientific significance and huge commercial value. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 :Preparation and characterization of Fe / Mn-SNC double single-atom nanomaterials. Figure 1 A: Flowchart of the synthesis process of Fe / Mn-SNC. Figure 1 B and Figure 1 C: Transmission electron microscopy (TEM) images clearly show that Fe / Mn-SNC has a Yolk-Shell structure, consisting of a rough, concave outer shell and an inner dense carbon layer. Similar phenomena can be observed on a larger scale by scanning electron microscopy. Figure 1 D: Energy dispersive X-ray spectroscopy mapping shows that Fe and Mn are uniformly dispersed, as are S, C, and N elements. Figure E: To further determine the dispersion of metal species on the yolk shell carbon framework, anomaly-corrected STEM (AC-STEM) was used. Figure F: The atomically dispersed bright spot pairs marked by yellow ovals can be assigned to heavier Fe-Mn double sites such as S, N, and C, confirming that the Fe-Mn pairs on the yolk shell carbon framework are indeed atomically dispersed. Figures G and H: To visualize the Fe-Mn atomic pairs, they were simulated using two-dimensional (2D) and three-dimensional (3D) resolution maps, respectively, and the results showed that the positions of the Fe-Mn pairs showed strong color signals.

[0028] Figure 2 :Multi-enzyme mimetic activity of Fe / Mn-SNC double single-atom nanomaterials. Figure 2 A: Schematic diagram of oxidase-like enzymes. It shows that Fe / Mn-SNC can oxidize the most common substrates TMB\OPD\ABTS under the action of O2 without adding H2O2. Figure 2 B: UV wavelength diagram for oxidation of three substrates. Figure 3C: Comparing the main sample with the control sample, the properties of the oxidase were compared using the oxidation of TMB as an example. Absorbance from high to low: Fe / Mn-SNC>Fe-N4S>Mn-N4S>Fe-N4>Mn-N4>Control. Figure 2 D: Schematic diagram of glutathione oxidation. Figure 2 E: Detect the ability of the main sample and the control sample to oxidize GSH. Absorbance from high to low: control>Mn-N4>Fe-N4>>Mn-N4S>Fe-N4S>Fe / Mn-SNC. The ability to consume GSH: Fe / Mn-SNC>Fe-N4S>Mn-N4S>Fe-N4>Mn-N4>control. Figure 2 F: GSH consumption capacity of the main sample. The enzyme amount of Fe / Mn-SNC was changed to 0, 10, 15, and 20 μg / mL. The kinetic curve of the GSH consumption capacity of the main sample was used to detect the decrease in absorbance between 0 and 400S. Figure 2 G: Schematic diagram of superoxide dismutase. Superoxide dismutase can react with O2 - The reaction produces H2O2. Figure 2 H: Principle curve of SOD kit for Fe / Mn-SNC. Figure 2 I: SOD kit for O2 - The higher the inhibition rate, the better the SOD-like activity. Figure 2 J: Schematic diagram of the reaction principle of H2O2 and TMB under the action of enzyme. Figure 2 K: Comparison of absorbance of Fe / Mn-SNC+H2O2+pH+TMB, Fe / Mn-SNC+pH+TMB, and pH+TMB. Figure 2 L: Compare the main sample with the control sample, and compare the properties of peroxidase-like enzymes using the oxidation of TMB as an example. Absorbance from high to low: Fe / Mn-SNC>Fe-N4S>Mn-N4S>Fe-N4>Mn-N4>Control. Figure 2 M: Summary of enzyme activity and Michaelis constant of peroxidase-like main sample and comparison sample. Figure 2 N: ESR measurement spectrum of peroxidase-like system. Figure 2 O: ESR measurement spectrum measured by oxidase-like system.

[0029] Figure 3 :Biocompatibility and in vitro antibacterial activity of Fe / Mn-SNC double single-atom nanomaterials. Figure 3 A: Survival rates of E.coil and MRSA after Fe / Mn-SNC treatment. Figure 3 B: Cell viability of L929 cells treated with Fe / Mn-SNC. Figure 3 C: Live / dead cell staining fluorescence images of L929 cells treated with Fe / Mn-SNC for 3 days. Figure 3D: Hemolysis results of NaCl, Triton X and Fe / Mn-SNC. Figure 3 E: Photos of MRSA and E.coil colonies after different treatments. Figure 3 F: SEM images of MRSA and E.coil after different treatments. The yellow arrows indicate the destruction of bacterial cell membranes. Figure 3 G: Live / dead cell staining fluorescence images of MRSA and E.coil after Fe / Mn-SNC treatment. Figure 3 H: Quantitative analysis of ROS in MRSA after Fe / Mn-SNC treatment. ****p<0.0001. Figure 3 I: UV-visible absorption spectra and photographs of DNTB in MRSA treated with Fe / Mn-SNC for different time periods. Figure 3 J: Survival rate of MRSA bacteria after adding different free radical scavengers.

[0030] Figure 4 :Efficacy of Fe / Mn-SNC double single-atom nanomaterials in treating MRSA-infected skin wounds. Figure 4 A: Schematic diagram of the mouse model and treatment process of MASR-infected skin wounds. Figure 4 B: Photos of mouse wounds at different treatment times. Figure 4 C: Changes in wound area of ​​mice after different treatments at different time periods (days 1, 5, 8, and 12). **p<0.01 and ****p<0.0001. Figure 4 D: Wound rheology diagrams of different treatments at different time periods. Figure 4 E: Agar plate photos of MRSA colonies with different treatments on days 1 and 12. Figure 4 F and Figure 4 G: H&E staining and Masson staining images of wound tissues of mice after different treatments on day 12. DETAILED DESCRIPTION

[0031] The present invention will be further described with reference to specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the scope of the present invention.

[0032] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased through regular channels.

[0033] The experimental methods in the following examples are conventional methods unless otherwise specified. The experimental materials used in the following examples are commercially available products unless otherwise specified.

[0034] Example 1: Preparation and characterization of Fe / Mn-SNC double single-atom nanomaterials

[0035] Preparation method:

[0036] Step 1: Preparation of powdered FeMn-MOF: Add 2.94g Zn(NO3)2·6H2O and 60mg Mn(OAc)2+60mg Fe(NO3)2·9H2O to 80mL anhydrous methanol at the same time and stir for 30min to prepare a metal precursor solution. Dissolve 3.24g 2-methylimidazole in 80mL methanol solution to prepare a ligand solution. Then, immediately add the above metal precursor solution to the above ligand solution and continue stirring for 5h. Wash three times with methanol and dry in a vacuum oven at 60°C overnight to obtain powdered FeMn-MOF.

[0037] Step 2: FeMn-SNC DASC was prepared by one-step pyrolysis strategy: 30 mg sulfur powder was uniformly mixed with 1 g dicyandiamide and loaded into a porcelain boat and placed in the upstream of the tube furnace. 100 mg FeMn MOF powder was placed in the porcelain boat and placed in the downstream of the tube furnace. Then, the mixture was heated at 1000 °C for 5 °C min. -1 The FeMn-SNC DASC was obtained by pyrolysis under Ar atmosphere at a rate of 2 h.

[0038] In the above preparation method, the specific preparation process of Fe / Mn-SNC is as follows Figure 1 As shown in A. Using Fe and Mn precursors as metal nodes and 2-methylimidazole as a coordination linker, a typical Fe-Mn bimetallic organic framework (FeMn-MOF) polyhedron was synthesized by self-assembly process in methanol solvent. Using a one-step pyrolysis method, sulfur powder and dicyandiamide were placed upstream of the tube furnace, and FeMn-MOF was placed downstream, and argon was passed through the high temperature pyrolysis at 1000°C for two hours. During the pyrolysis process, the original ordered structure of MOF will be destroyed, the etching of the MOF surface structure by the gas S ligand will be accelerated, and the initial shrinkage of the MOF cavity will be promoted. N2 promotes the shrinkage of the internal carbon layer, forming an egg yolk shell structure with a graphene-like framework on the surface and a carbon core inside. Due to the precise control of the feed, atomic-level Fe and Mn can be accurately formed. Quantitatively, inductively coupled plasma emission spectroscopy (ICPOES) confirmed that the mass ratio of Fe (1.35wt%) and Mn (1.24wt%) was close to 1:1.

[0039] Transmission electron microscopy (TEM) and high-angle annular dark field scanning TEM (HAADF-STEM) images clearly show that the Fe / Mn-SNC has a yolk-shell structure (Figures B and C), consisting of a rough and concave outer shell and an inner dense carbon layer. Energy dispersive X-ray spectroscopy (EDS, Figure D) mapping shows that Fe and Mn are uniformly dispersed, as are S, C, and N elements, providing evidence for the successful incorporation of sulfur into the carbon material. To further determine the dispersion of metal species on the yolk-shell carbon framework, anomaly-corrected STEM (AC-STEM) was used to analyze the Fe / Mn-SNC, see Figure E. As shown in Figure F, many bright Fe and Mn double single atoms are uniformly dispersed, represented by yellow circles. Analysis of the diatomic distance between Fe-Mn showed that there is a direct interaction between Fe and Mn atoms. To visualize the Fe-Mn atomic pairs, three-dimensional (3D) and two-dimensional (2D) resolution maps were made, respectively, and the results showed a strong color signal representing the location of the Fe-Mn pairs, as shown in Figures G and H.

[0040] Example 2: Multi-enzyme mimetic activity of Fe / Mn-SNC double single-atom nanomaterials

[0041] In Example 2, the multi-enzyme mimetic activities of the Fe / Mn-SNC prepared in Example 1 were studied, including oxidase (OXD)-like, glutathione oxidase (GPx)-like, superoxide dismutase (SOD)-like, and peroxidase (POD)-like activities.

[0042] We first evaluated the OXD-mimetic activity of Fe / Mn-SNC, which can catalyze the oxidation of the most common chromogenic substrates (TMB, OPD, and ABTS) in the presence of O2. Figure 2 As shown in A, in the absence of any oxidant, Fe / Mn-SNC can rapidly oxidize O2 to produce ·O2 - , making the colors of OPD, TMB, and ABTS change from colorless to yellow, blue, and green, and the characteristic peaks appear at 417, 652, and 420 nm in the UV-visible absorption spectrum ( Figure 2 B) In Figure 2In C, the absorbance of the five catalysts was compared using the oxidation substrate TMB as an example. The experimental order of oxidase-like activity was Fe / Mn-SNC>Fe-N4S>Mn-N4S>Fe-N4>Mn-N4>control. Obviously, Fe / Mn-SNC has significantly higher oxidase-like activity than other reference catalysts. It is well known that the presence of GSH (0.1-10mM) in bacterial cells can neutralize ROS and reduce the antibacterial efficiency. Therefore, the consumption of GSH can enhance the ROS-based antibacterial effect. As the concentration of Fe / Mn-SNC increased, the absorption intensity at 412nm decreased significantly, confirming its activity in mimicking GPx ( Figure 2 F). In addition, Fe / Mn-SNC showed intrinsic SOD mimetic activity, which could be seen from the - This was demonstrated by measurements of the consumption of produced hydrogen peroxide ( Figure 2 G) Experiments show that O2 - Nitro blue tetrazolium (NBT) can be reduced to blue formate, which has a characteristic absorption peak at about 600nm. Fe / Mn-SNC can eliminate ·O2 - , inhibiting the formation of formate, resulting in a decrease in absorbance compared to the control (in the absence of Fe / Mn-SNC) ( Figure 2 H). The higher the inhibition rate, the better the SOD-like activity. The order of SOD-like activity of the samples is Fe / Mn-SNC>Fe-N4S>Fe-N4>Mn-N4S>Mn-N4( Figure 2 I). The POD mimicking activity of Fe / Mn-SNC was detected by TMB oxidation colorimetry. Fe / Mn-SNC effectively catalyzed the generation of ·OH( Figure 2 J) Figure 2 As shown in Figure k, the Fe / Mn-SNC-TMB group has an obvious absorption peak at 652nm, and the absorption peak of Fe / Mn-SNC-TMB-H2O2 at 652nm can be further enhanced. The specific activity (SA) was measured to verify the synergistic catalytic effect between Fe and Mn single atoms. Figure 2 As shown in Figure 2, the SA of Fe / Mn-SNC (54.63 U / mg) is higher than that of Fe-N4S (35.70 U / mg), Mn-N4S (11.34 U / mg), Fe-N4 (2.16 U / mg) and Mn-N4 (0.62 U / mg), respectively, indicating that Fe / Mn-SNC has excellent enzymatic properties. The effects of Fe and Mn diatomic sites on enzyme activity and on the steady-state kinetics of the main sample (Fe / Mn-SNC) and reference groups (Fe-N4S, Mn-N4S, Fe-N4 and Mn-N4) were studied. Figure 2As expected, the Michaelis constant (K) of the Fe / Mn-SNC nanozyme for TMB substrate was m , 0.17mM, V max ,47.46×10 -8 Ms -1 ) and the Michaelis constant (K m , 18.79mM, V max , 95.37×10 -8 Ms -1 ) are better( Figure 2 M). To evaluate the cooperative enzyme catalytic mechanism of electron spin resonance (ESR), the ROS generated during the reaction were characterized by electron spin resonance (ESR) and fluorescence. According to previous reports, the capture reagent 5,5-dimethyl-1-pyrrolidine N-oxide (DMPO) was used to verify the active species (·O2 - and ·OH). Figure 2 In addition to detecting ·O2 with a specific six-peak pattern, - In addition, in the absence of hydrogen peroxide, ·OH with a specific four-peak pattern was also measured by ESR of an OXD-like reaction. Therefore, the inventors' hypothesis that Fe / Mn-SNC has multiple enzyme-like properties is confirmed, and part of the generated ·O2 - is decomposed into hydrogen peroxide. Similarly, ·OH( Figure 2 O).

[0043] Example 3: Biocompatibility and in vitro antibacterial activity of Fe / Mn-SNC double single-atom nanomaterials

[0044] The minimum inhibitory concentration of Fe / Mn-SNC was investigated using Gram-negative bacteria-Escherichia coli (E. coli) and Gram-positive bacteria-methicillin-resistant Staphylococcus aureus (MRSA) as representative strains. The results showed that when the concentration of Fe / Mn-SNC reached 100 μg mL -1 The survival rate of both strains was less than 5%, which proved that it had good antibacterial effect. -1 The Fe / Mn-SNC was used in subsequent experiments ( Figure 3 A).

[0045] Good biocompatibility is an important factor in the development of biomaterials. In the first part of the experiment, the cell proliferation-cytotoxicity assay kit (CCK-8) was used to evaluate the cytotoxicity of the minimum inhibitory concentration of Fe / Mn-SNC. L929 cells from ATCC were incubated with 100 μg mL -1After incubation with Fe / Mn-SNC for 1, 2, and 3 days, the results showed that during the three-day culture period, there was no significant difference in the cell survival rate between L929 cells co-cultured with Fe / Mn-SNC and blank control L929 cells, and the cell survival rate was above 95% ( Figure 3 B). In order to further observe the effect of Fe / Mn-SNC on L929 cell proliferation, cells co-cultured with Fe / Mn-SNC for 1, 2, and 3 days were fluorescently stained. The staining results showed that during the 3-day culture period, L929 cells maintained a healthy cell morphology, and the cell number increased day by day, showing good proliferation activity ( Figure 3 C). This indicates that Fe / Mn-SNC has good biocompatibility at the cellular level.

[0046] In addition, in vitro hemolysis test was used to evaluate the blood compatibility of Fe / Mn-SNC. Figure 3 The picture in D shows the obvious difference in color between the negative control (NaCl), Fe / Mn-SNC, and the positive control (Triton X). The color of the Fe / Mn-SNC group is transparent, similar to the negative control group, while the Triton X group is bright red. The quantitative results show that the hemolysis rate of the Fe / Mn-SNC group is very low (2.68%), which is not significantly different from the negative control group, indicating that Fe / Mn-SNC has good blood compatibility.

[0047] In the second part of the experiment, the antibacterial activity of Fe / Mn-SNC against MRSA and E.coli was first studied using the plate culture method. Figure 3 The results showed that no colonies were formed in the Fe / Mn-SNC and Ag groups, while a large number of colonies still grew in the untreated bacteria. This indicates that Fe / Mn-SNC has a good antibacterial effect on both MRSA and E. coli. In order to further explore its antibacterial properties, the morphology of bacteria was observed using a scanning electron microscope, such as Figure 3 As shown in F, the surfaces of MRSA and E. coli were smooth before treatment, spherical and rod-shaped, respectively. In contrast, the surfaces of the two bacteria treated with Fe / Mn-SNC became rough and wrinkled or severely cracked, losing their complete skeletons, and even causing some adjacent bacteria to adhere to each other. The yellow arrows indicate different degrees of damage. At the same time, confocal laser scanning microscopy (CLSM) was used to visually evaluate the antibacterial activity of Fe / Mn-SNC, and the bacteria were stained using a bacterial live / dead staining kit. The stained live bacteria appear green, and the dead bacteria appear red. Figure 3As shown in G, before Fe / Mn-SNC treatment, almost all bacteria were alive, and after 2 h of Fe / Mn-SNC treatment, clear red fluorescence was observed for both MRSA and E. coli, indicating that most bacteria were killed. These results confirm that Fe / Mn-SNC has good antibacterial activity against MRSA and E. coli.

[0048] In addition, the antibacterial mechanism of Fe / Mn-SNC was further explored. To evaluate the production of ROS, dichlorofluorescein (DCFH-DA) was used as an indicator of ROS in bacteria. Compared with the untreated group, the fluorescence intensity of MRSA after Fe / Mn-SNC treatment increased by 2.2 times, indicating that Fe / Mn-SNC induced MRSA strains to produce ROS ( Figure 3 H). It is well known that high glutathione (GSH) levels at the site of bacterial infection may consume a large amount of ROS produced by nanozymes. Therefore, consuming GSH at the site of infection can enhance the antibacterial therapeutic effect. The results of the GSH detection kit showed that the concentration of GSH decreased with the increase of the incubation time of MRSA with Fe / Mn-SNC, indicating that Fe / Mn-SNC has an effective GSH consumption ability ( Figure 3 I) The free radical scavenging experiment results show that H2O2, ·OH, ·O2 - and 1 After O2 was removed, the survival rate of MRSA bacteria increased, which indicated that H2O2, ·OH, ·O2 - and 1 O2 and other free radicals play a vital role in the antibacterial process of Fe / Mn-SNC ( Figure 3 J).

[0049] These results are consistent with the above-mentioned enzymatic catalytic activities and antibacterial properties, and fully demonstrate that Fe / Mn-SNC has good multi-enzyme bactericidal properties, can produce abundant toxic ROS and consume GSH. It is worth noting that Fe / Mn-SNC has a wide range of antibacterial effects.

[0050] Example 4: Efficacy of Fe / Mn-SNC double single-atom nanomaterials in treating MRSA-infected skin wounds

[0051] Inspired by the excellent antibacterial activity of Fe / Mn-SNC in vitro, the inventors constructed a skin wound mouse model of MASR infection and evaluated the in vivo therapeutic effect of Fe / Mn-SNC ( Figure 4A). Female Balb / C mice aged 6-8 weeks were selected and provided by Beijing Weitonglihua Experimental Animal Technology Co., Ltd. and placed in the Animal Barrier Laboratory of the Chinese Institute of Rehabilitation Sciences under controlled conditions. Specifically, MASR-infected wounds with a diameter of approximately 0.8 cm were established on the back of the mice, and wound photos under different treatments were provided to evaluate the healing progress. The experimental animals were randomly divided into PBS group, Ag treatment group and Fe / Mn-SNC treatment group, with 5 mice in each group.

[0052] It is noteworthy that the wound area of ​​the Fe / Mn-SNC group decreased significantly faster than that of the PBS and Ag groups, showing faster wound healing and less scarring on day 12 ( Figure 4 B. Figure 4 C. Figure 4 D) The wound tissues of mice were collected on the 1st and 12th days of treatment for plate counting experiments. Figure 4 The photo in E shows that on the first day of treatment, all three groups produced a large number of colonies, indicating the successful construction of the MRSA infection model. However, on the 12th day of treatment, the number of colonies in the Fe / Mn-SNC group was significantly lower than that in the other groups, which explains why the wound healing in the Fe / Mn-SNC group was the fastest.

[0053] Subsequently, hematoxylin-eosin (H&E) and Masson staining were used to observe the histological changes of the wound surface of mice after different treatments for 12 days to further evaluate the wound healing. The results showed that the wound surface of the Fe / Mn-SNC group showed no signs of inflammation, with more new hair follicles and a more complete epidermis ( Figure 4 F), collagen fibers are denser ( Figure 4 G). These results indicate that Fe / Mn-SNC treatment has a better bactericidal effect, thereby promoting wound healing.

[0054] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing Fe / Mn-SNC double single-atom nanomaterials with multi-enzyme activity, characterized in that: The preparation method comprises the following steps: Step 1: Preparation of powdered FeMn-MOF: 1-5 g Zn(NO3)2·6H2O, 20-80 mg Mn(OAc)2 and 20-80 mg Fe(NO3)2·9H2O are added to 50-100 mL organic solvent at the same time, stirred to prepare a metal precursor solution; 1-5 g 2-methylimidazole is dissolved in 50-100 mL organic solvent to prepare a ligand solution; then, the metal precursor solution is immediately added to the ligand solution, stirred continuously, washed several times with an organic solvent, and dried in a vacuum oven overnight to obtain powdered FeMn-MOF; Step 2: Preparation of FeMn-SNC double single atom (DASC) by one-step pyrolysis strategy: 10-50 mg sulfur powder was uniformly mixed with 0.5-5 g dicyandiamide and loaded into a porcelain boat and placed in the upstream of the tube furnace. 50-150 mg FeMn MOF powder was placed in the porcelain boat and placed in the downstream of the tube furnace. Then, the mixture was heated at 800-1200 °C for 5 °C min -1 The FeMn-SNC DASC was obtained by pyrolysis in Ar atmosphere at a rate of 1.5 %.

2. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: Step 1: Preparation of powdered FeMn-MOF: Add 2-4 g Zn(NO3)2·6H2O, 50-70 mg Mn(OAc)2 and 50-70 mg Fe(NO3)2·9H2O to 70-90 mL organic solvent at the same time, stir for 20-40 min to prepare a metal precursor solution; dissolve 2-4 g 2-methylimidazole in 70-90 mL organic solvent to prepare a ligand solution; then, immediately add the above metal precursor solution to the above ligand solution, continue stirring for 4-6 h, wash with organic solvent several times, and dry in a vacuum oven overnight to obtain powdered FeMn-MOF; Step 2: Preparation of FeMn-SNC DASC using a one-step pyrolysis strategy: 20-40 mg sulfur powder was uniformly mixed with 0.5-2 g dicyandiamide and loaded into a porcelain boat and placed in the upstream of the tube furnace. 80-120 mg FeMn MOF powder was placed in the porcelain boat and placed in the downstream of the tube furnace. The mixture was then heated at 900-1100 °C for 5 °C min -1 The FeMn-SNC DASC was obtained by pyrolysis in Ar atmosphere at a rate of 1 to 5 h.

3. The preparation method according to claim 1, characterized in that: The organic solvent is methanol.

4. The Fe / Mn-SNC double single-atom nanomaterial prepared by the preparation method described in any one of claims 1 to 3.

5. The nanomaterial according to claim 4, characterized in that: The nano material has a Yolk-Shell structure.

6. The nanomaterial according to claim 4, characterized in that: The multi-enzyme activity includes oxidase (OXD)-like, glutathione oxidase (GPx)-like, superoxide dismutase (SOD)-like and peroxidase (POD)-like activities.

7. Use of the nanomaterial according to any one of claims 4 to 6 in the preparation of an antibacterial agent for removing bacteria.

8. The use according to claim 7, characterized in that: The antibacterial agent has a broad-spectrum antibacterial effect.

9. The use according to claim 7, characterized in that: The bacteria included Escherichia coli and methicillin-resistant Staphylococcus aureus (MRSA).

Citation Information

Patent Citations

  • Ultrasonic synthesis method and application of different single-metal and double-metal two-dimensional MOFs nano-enzymes

    CN111330643A

  • Preparation method and application of bimetallic nano-enzyme

    CN114345349A

  • Preparation method and application of phosphorus-sulfur-doped bimetallic MOF composite nano-enzyme with multi-enzyme activity

    CN116899597A

  • Monatomic nano-enzyme and preparation method thereof

    CN117398407A

  • Bimetal MOFs (Metal-Organic Frameworks) nano-enzyme hydrogel compound as well as preparation method and application thereof

    CN117959488A

Cited By

  • Application of Fe / Mn bimetallic enzyme in preparation of anti-periodontitis preparation or tooth whitening preparation

    CN122075534A

  • Preparation method and application of nitrogen-doped carbon nanotube loaded Fe / Mg diatomic nanoscale enzyme

    CN122805827A